Botulinum Neurotoxins - Rummel, Andreas; Binz, Thomas; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
Botulinum neurotoxins are the most toxic natural substances and represent a major threat to the population when intentionally released in bioterrorist attacks. On the other hand, during the past two decades botulinum neurotoxins have become established as indispensable drugs for the treatment of a variety of severe neurological disorders. The need for efficient countermeasures as well as the expansion into additional fields of therapeutic application, call for comprehensive information on the botulinum neurotoxin molecules and their mode of action. Our knowledge of this subject has made great strides in recent years, setting the stage for the development of new botulinum neurotoxin-based molecules and novel applications. This book reviews the current status of basic botulinum neurotoxin research. The first part describes the genetic variability of the toxin-producing bacteria, and sheds light on each step from toxin ingestion to the abrogation of synaptic signaling including the intestinal passage and absorption, nerve cell binding and entry, and intracellular substrate cleavage. The remaining chapters detail progress made in detection methods for botulinum neurotoxins, the development of botulinum neurotoxin inhibitors, and strategies to refine the neurotoxins for further medicinal applications by means of recombinant technologies.
Keywords: Medicine; Neurosciences; Toxicology; Biomedicine; Pharmacology/Toxicology.; Neurosciences